(untitled) (Scientific journal of the Fergana State University, 2025)
This paper is dedicated to the study of the image system and poetics of folk legends, focusing on the Uzbek and English folkloric traditions. The central focus is on the primary images, their roles, and peculiarities in the context of mythological, historical, and natural symbols used in these legends. The study includes a comparative analysis of poetic devices and symbols, such as the use of mythical beings, natural phenomena, animals, and historical characters. Special attention is given to how images in Uzbek and English folk legends not only reflect the cultural and worldview aspects of these peoples but also serve to convey moral and philosophical values through poetic forms. The research aims to identify similarities and differences in the approaches to creating images and their integration into the overall plot of folk narratives. This study will be valuable for specialists in folklore, literary studies, and cultural studies, as well as anyone interested in mythology and folk traditions.